SOSIALIASI PEMANFAATAN TEKNOLOGI DIGITAL DALAM PENJUALAN TOKO DI SHOPEE UNTUK MENDUKUNG PEMASARAN UMKM DI DESA DANGDANG - Ria Ester; Agung Siswopranoto; Galuh Saputri (Abdi Jurnal Publikasi, 2023)
Today's technology continues to grow and the benefits of using the internet are felt for the users. Some people feel dependent on the internet, including the activities of Micro, Small and Medium Enterprises (MSMEs) in utilizing information technology to run their business, especially in the digitalization era. Regional superior products have the potential to be further developed according to natural conditions and the local environment, so that they can be competitive and can improve people's welfare. Regional superior products, are products in the form of services and goods with uniqueness or characteristics at the village level or at the village, sub-district, district and provincial levels, which are produced by MSMEs. Application of science and technology from universities as an effort to develop regional superior products, so that they are competitive in the domestic market and even reach dynamic foreign countries. Through community service activities, Pamulang University lecturers in the Informatics Engineering study program took a role in socializing the role of information and communication technology in socialization activities on the use of digital technology in viewing products and taking shop sales results at Shopee to support MSME marketing. and helping the MSME community in Dangdang Village, Tangerang. in developing its business to improve marketing. By studying the use of the Shopee marketplace, it is hoped that Dangdang Village women will develop marketing skills through the Shopee marketplace to compete in the outside world in order to become successful and competent, increase their creativity and quality of work so that it is useful for them and the community.